Cyclization of the Semicarbazones to 1,3,4-Oxadiazole Derivatives Using Ceric Ammonium Nitrate as Oxidant - Vahedi, H.; Lari, J.; Bav, A.; Ameri, B. (Asian Journal of Chemistry, 2011)
Cyclization of the semicarbazones to 1,3,4-oxadiazole using ceric ammonium nitrate as oxidant was studied. 2-Imino-1,3,4-oxadiazolines can be produced from semicarbazones, which undergo thermolysis to amides. Benzoic acid benzylidene hydrazide can also be cyclized to 2-methoxy- 2-phenyl-1,3,4-oxadiazole in the presence of ceric ammonium nitrate and methanol.